Exposure to Mebendazole and Pyrvinium during Pregnancy: A Danish Nationwide Cohort Study. (18th September 2012) - Torp-Pedersen, A.; Jimenez-Solem, E.; Andersen, J. T.; Broedbaek, K.; Torp-Pedersen, C.; Poulsen, H. E.
Abstract : Purpose . Families with children are frequently exposed to pinworm infection and treatment involves the whole family. Information on consequences of exposure during, pregnancy is limited. The aim of this study was to investigate the exposure to pyrvinium and mebendazole before, during, and after pregnancy in a Danish nationwide cohort. Methods . From nationwide administrative registers, we identified 718, 900 births in Denmark between January 1997 and December 2007 as well as maternal prescription data of anthelmintics and maternal characteristics. Redemption of a prescription for pyrvinium or mebendazole was used to identify exposure. Results . 4715 women redeemed a prescription for pyrvinium or mebendazole during pregnancy; 1606 for pyrvinium, 2575 for mebendazole, and 534 for both drugs. Having >2 children compared to having no previous children was associated with exposure to pyrvinium (OR: 7.1, 95% CI: 5.8–8.7) and mebendazole (OR: 20.8, 95% CI: 17.3–24.9). Conclusion . 4715 pregnant women redeemed a prescription for either mebendazole or pyrvinium. We believe the exposure to be even higher since pyrvinium is also sold over-the-counter. Limited information on birth outcomes is available at present time, and considering the number of exposed pregnancies, we recommend that studies are to be undertaken to assess the safety of pyrvinium and mebendazole during pregnancy.